2004
DOI: 10.1212/01.wnl.0000138440.39918.0c
|View full text |Cite
|
Sign up to set email alerts
|

Motor signs during the course of Alzheimer disease

Abstract: Background-Motor signs (MOSIs) are common in Alzheimer disease (AD) and may be associated with rates of cognitive decline, mortality, and cost of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
174
2
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(190 citation statements)
references
References 49 publications
8
174
2
6
Order By: Relevance
“…Alterations in facial expression, gait and posture, and manifestations of rigidity, bradykinesia, and tremor are found in late AD stages although mounting evidence suggests that motor problems emerge long before any recognizable sign of AD (Wilson et al ., 2000; Scarmeas et al ., 2004; Buchman & Bennett, 2011). Tau abnormal hyperphosphorylation and subsequent malfunction are postulated as crucial mechanisms in AD neuronal dysfunction where hyperphosphorylated and/or aggregated (insoluble) forms of Tau exhibit neurodegenerative action(s) that also interfere with normal Tau, sequestering and reducing soluble Tau forms (Ksiezak‐Reding et al ., 1988; Zhukareva et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in facial expression, gait and posture, and manifestations of rigidity, bradykinesia, and tremor are found in late AD stages although mounting evidence suggests that motor problems emerge long before any recognizable sign of AD (Wilson et al ., 2000; Scarmeas et al ., 2004; Buchman & Bennett, 2011). Tau abnormal hyperphosphorylation and subsequent malfunction are postulated as crucial mechanisms in AD neuronal dysfunction where hyperphosphorylated and/or aggregated (insoluble) forms of Tau exhibit neurodegenerative action(s) that also interfere with normal Tau, sequestering and reducing soluble Tau forms (Ksiezak‐Reding et al ., 1988; Zhukareva et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Extrapyramidal signs (e.g., bradykinesia, rigidity, and reduced facial expression) are seen in 30% of cases; however, rest tremor is rare (Scarmeas et al 2004). Gait disturbances become more prominent with disease progression and are associated with a substantially higher risk for falls.…”
Section: Neurological Examinationmentioning
confidence: 99%
“…188 Dementia is estimated to occur in 30% of patients with PD, 6 and a large longitudinal study of AD patients found that at least one motor sign of PD was detected in 44% of patients during at least one of their study visits. 189 Because of this overlap, several studies have evaluated whether APOE genotype is a risk factor for PD.…”
Section: Apoementioning
confidence: 99%